Cross-reactive influenza-specific antibody-dependent cellular cytotoxicity-mediating antibodies in HIV-infected Indian individuals. Issue 1 (2nd January 2018) - Nehul, Sanketkumar; Kulkarni, Archana; Pawar, Shailesh; Godbole, Sheela; Ghate, Manisha; Thakar, Madhuri
Abstract: Background: The influenza-specific antibodies mediating antibody-dependent cellular cytotoxicity (ADCC) may be important in protection against influenza. However, it is not known whether immunocompromised individuals such as HIV-infected persons who have never been vaccinated with influenza vaccine have such a response. Methods: The anti-influenza ADCC responses were investigated in plasma samples from 50 HIV positive persons [25 long-term nonprogressors (LTNPs) and 25 progressors] and from 20 HIV-uninfected healthy individuals. None of the participants had received influenza vaccine. Results: The frequencies and the magnitude of ADCC responses against two influenza A virus strains (pH1N1-A/California/7/2009 and H3N2-A/Brisbane/10/2007) were comparable in HIV-infected individuals and in healthy controls ( p  > .05). However, the magnitude of the ADCC response was slightly higher in LTNPs than in progressors ( p  = .025). The level of ADCC antibodies against pH1N1 and H3N2 correlated significantly indicating the cross-reactive nature of these antibodies ( p  < .0001). Additionally, the level of these ADCC antibodies was significantly associated with antibodies against the highly pathogenic avian influenza H5N1 virus (H5N1-A/Chicken/India/NIV/33487/2007). Conclusion: This is the first report of anti-influenza ADCC antibodies in HIV-infected Indian individuals. Identification of cross-reactive ADCC epitopes in HIV-infected individuals could improve the design of influenza vaccine for immunocompromised individuals.